Revitatlizing downtown Cebu City through redeveloping Carbon Public Market - Arnaiz, Victoria Elspeth R.; Varon, Maria Faith (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
This research focuses on the revitalization of the urban fabric of downtown Cebu City through redeveloping the existing Carbon Public Market located in the area. Cebu City and its growth towards becoming a metropolitan center has brought different changes to its urban landscape. One of which brings to concern, the continuing urban decay in the city's downtown area. The downtown district of Cebu City is rich in historical and local culture which is an important factor in the city's urban landscape. To keep the downtown district from its continual decay, the project focuses on using the Carbon Public Market as a tool to bring back the life and activity in downtown Cebu City. Through methods of site analysis, interviews, site visits and other data collection methods, this project is brought to a step by step design research where the end product of the thesis is creating a public market that would encourage different activities that would bring people back and life to the downtown district of Cebu City.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman